Sistemas técnicos agrícolas e cafeicultura científica globalizada no sul de Minas Gerais - Fernandes, Carlos Alberto [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The study aims to analyze the mechanization of the main coffee growing region in the south of Minas Gerais, in force, especially from the 1970s. But you get new content from the1990s, with the introduction of new information technologies. The use of machines in production processes appear as one of the great transformations of coffee in the period modern after globalization, requiring a labor more specialized, although resulting in unemployment in rural areas. So in the period of globalization new technologies gradually replace manual work. In the coffee farm, the old ways of the production (that handed down from father to son) aren't accepted by the global scientific agriculture (Santos, 2000:88). They are considered inefficient and low quality, but not attendant of patterns the international market. The national companies producing agricultural machines for coffee with emphasis on the company Pinhalense Agricultural Machinery SA believe that the producers of the region are its biggest customers in the country, considering the degree of mechanization more pronounced compared to other coffee growing regions. Analyze the importance of the coffee region with a contribution in the indicators of export and trade surplus in the Brazil and State of Minas Gerais

O trabalho tem como objetivo principal analisar a mecanização da cafeicultura na região do Sul de Minas Gerais, em vigor, sobretudo, a partir da década de 1970. Mas, que adquire um novo conteúdo a partir da década de 1990, com a introdução das novas tecnologias da informação. A utilização de máquinas nos processos produtivos surge como uma das grandes transformações da cafeicultura moderna pós globalização, exigindo uma mão-de-obra mais especializada, mas resultando no aumento do desemprego no campo. No atual mundo globalizado, as novas tecnologias substituem gradativamente os trabalhos manuais. Na cafeicultura, as antigas formas de produção, transmitidas de pai para filho, não são mais aceitas pela agricultura científica globalizada (SANTOS, 2000:88). Elas são consideradas ineficientes e de baixa qualidade, não atendendo aos padrões de eficiência que o mercado internacional exige. As empresas nacionais produtoras de máquinas agrícolas para a cafeicultura com destaque para a empresa Pinhalense Máquinas Agrícolas S.A consideram que os produtores da região são seus maiores clientes no país, considerando o grau de mecanização mais acentuado em relação a outras regiões produtoras de café. Analisa-se a importância da cafeicultura da região, com grande contribuição nos indicadores de exportação e no superávit da balança comercial do país e de Minas Gerais
Keywords: Café - Cultivo; Mecanização agrícola; Geografia econômica - Agricultura; Geografia agrícola; Minas Gerais, Sul; Coffee plantations; Farm mechanization; Economic geography; Agricultural geography